Ensuring the Quality and Efficiency of Education Through the Implementation of Digital Technologies in the Educational Process (Open Herald: Periodical of Methodical Research, 2023)
In this article, ensuring the quality and efficiency of education through the promotion of digital technologies in the educational process, providing a more interesting and interactive educational experience for students based on digital education, better understanding of students, better learning and understanding recommendations are given for the use of various digital tools such as videos, animations, simulations and games